ROLE OF SEASONAL CHANGES IN AFLATOXIN B1 CONTAMINATION IN COMPOUND CATTLE FEEDS IN KERALA, INDIA. - Chammakalayil Sukumaran Arun , Dr Pambayan Ulagan Mahalingam , Dr Haris Parengal . (Chelonian Research Foundation, 2024)
Aflatoxin B1 (AFB1) is the most toxic and primarily produced mycotoxin in Agricultural products around the globe, and its consumption causes life-threatening effects in humans and animals. Similarly, contaminated animal feeds will carry the toxin to animal products, like milk, eggs, and meat. This study discusses the role of seasonal changes in the contamination of Aflatoxin B1 in three branded compound cattle feeds in Idukki, Kollam, and Palakkad districts in Kerala, India. The study revealed that the monsoon (South Western Monsoon (SWM) and North East Monsoon (NEM)) cause elevated Aflatoxin B1 in the compound cattle feeds. On average, 65.28% of the total samples comply with the Bureau of Indian Standards (BIS) of AFB1 (20 µgkg-1) in compound cattle feeds, while the European Commission regulation (5 µgkg-1) satisfies only 17.36%. Moreover, a significant correlation was observed between Water activity (aw) and AFB1 in the compound cattle feed. The safe Water activity (aw) of more than 95% of the samples confirmed that AFB1 contamination occurred in the raw materials, not the compound cattle feeds. The theoretical extrapolation of Aflatoxin M1 from Aflatoxin B1 content in the tested samples pointed out that the cattle feed tested did not produce beyond the limit of FDA/Codex regulation for Aflatoxin M1 (0.5 µgkg-1) in the milk by the intake of compound cattle feeds maximum of 6 kg day-1 at the reported AFB1 contamination rate. This study will provide insights into AFB1 contamination throughout various seasons in compound cattle feeds in three districts in Kerala and its subsequent carryover into milk. Keywords: Aflatoxin, Aspergillus, Carcinogenicity, seasonal changes, compound cattle feeds, Water activity